Efeito de diferentes métodos de higienização na remoção de um adesivo para prótese e na redução da microbiota bucal de usuários de prótese total: estudo in vivo - Nunes, Élen Massaro [UNESP] (2015)
This study evaluated in vivo (n=20) the effectiveness of different cleaning methods in removing an adhesive for dentures (Ultra Corega cream) and the reduction of microorganisms in the oral microbiota. The cleaning methods were brushing the dentures with soft bristle brush using: A (room temperature water), B (water at room temperature + coconut soap), C (room temperature + dentifrice in water) and D (water+immersion in sodium perborate solution for 5 minutes). Saliva samples were taken before and after using the adhesive and realization of cleaning methods. The inner surfaces of the upper dentures were stained with 0.4% indigo carmine and the adhesive-covered areas were quantified (%) by means of a photographic method and assistance for a software (Image Tool). For microbiological analyzes the collected saliva was diluted and plated in a medium non-selective medium (Mueller Hinton Agar) and culture media for Candida spp (Sabouraud Dextrose Agar and CHROMagar Candida). After the incubation period (48 hours / 37°C), Candida species were identified and the number of colony forming units (CFU / ml) were calculated. It was concluded that the brushing combined with the immersion of the prosthesis into sodium perborate was more effective in removing the adhesive as compared with brushing with water (Dunn, p=.004). For the non selective media (ANOVA,p>0,05) and selective for Candida spp (Friedman, p>0,05), there was no influence of the cleaning methods on the oral microbiota.